How gender and personality traits influence job preferences among students in Norway and Poland - Leiv Opstad; Gurid Gjøstein Karevoll; Dagmara Lewicka; Torbjørn Årethun (Cogent Business & Management, 2024)
The article explores job preferences among business students through the lens of the Big Five personality traits, which have implications for students' attitudes. This investigation is conducted within the contexts of Norway and Poland, facilitating a comparative analysis of students from these two nations. Empirical evidence comprises responses to questionnaires gathered from 178 Polish students and 147 Norwegian students. By juxtaposing mean values and employing regression models, we scrutinized the link between personality traits and job preferences in both countries. The findings revealed that personality traits exhibit correlations with students' job preferences, with a particularly notable impact observed in the domain of agreeableness. This trait demonstrates a positive association with job security, work-life balance, teamwork and societal contribution. Moreover, the effect varies between Norwegian and Polish students, with discernible gender discrepancies. Through this comparative examination, the study highlights the mediating influence of society on the relationship between personality traits and job preferences among business students. It emphasizes the imperative for future investigations to integrate cultural and societal factors into their analyses when exploring the impact of personality traits on job preferences.
Keywords: 650; Job preferences; business students; personality traits; gender; work-life balance; career